PENGELOLAAN HUTAN PULAU SEHO SEBAGAI MODEL KONSERVASI PULAU KECIL DI KABUPATEN PULAU TALIABU - Murianto Wenno; Agustinus Kastanya; Iskar Iskar (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Forest area of Seho island was damaged. Mostly caused by the activities of people who live in and around the area. The activities were logging, wild animal hunting, as well as shifting cultivation. This activity is also supported by the community easy access into the forest. Community activities are threats to the existence of flora and fauna in the region. Agroforestry is a land use system by combining a variety of agricultural crops and forestry. The purpose of this study is to examine management of Seho Island with zoning approach and conduct management of multi-party collaboration. This study included a qualitative study, using the case study methodology. Selection of the sample (key informants) done intentionally (purposive sampling), by taking a sample of respondents by purposive sampling as many as 30 families. The results showed that managed Seho Island neighborhood zoning approach, namely 1. The core areas Seho Island nature reserve, 2. Buffer areas which is the area surrounding the core region (region Nature Reserve), which is generally found agroforestry plantation society, especially Plant cloves and Other forest plants, 3. Transition areas / Sustainable Development is an area outside the buffer zone on the public lands, beaches and coast, where the activity is intended for community economic development and regional economic development. In addition, the activities of multi-party collaboration is a necessity in the management of conservation areas Seho Island.